Taxonomy of tertiary education campus planning - Terro, Mohamad Jamil; Soliman, Ashraf Mohamed; Angell, Jerrell (Journal of Architecture and Urbanism, 2021)
This paper aims to present and discuss phases of planning and designing campuses for Higher Education Institutions (HEIs). The authors argue that creating a taxonomy to control an environment conducive to learning is of the same order of importance as that for education as depicted by Bloom, given the size, financial burden, and influence on learning outcomes. A specific model is proposed for the taxonomy of planning campuses for HEIs with four ordered phases: educational programming, spaces programming, master planning, and detailed design. The researchers followed four methodologies to support the proposed model: A literature review to seek relevant knowledge and terms used in previous studies; a descriptive discussion of the proposed campus planning and design taxonomy model; a survey of experts in educational and campus planning to examine the proposed phases; and, a case study of the campus of Kingdom University in Bahrain where the phases of taxonomy were implemented. This latter case study further exhibits how the executed campus planning process is developed in adherence with state-of-the-art educational demands and trends. This paper is concluded with guidelines of HEIs campus planning as illustrated a diagram for the proposed model of taxonomy showing the process and illustrating the model domains, together with its phases and planning process considerations. The model also analyses the relationship between the domains that are ordered according to the process flow starting with educational programming up to the detailed design phases.